ON STATES WITH ABSORBING TENDENCIES IN SELF-ORGANIZING MAPS WITH INPUTS IN AN INNER PRODUCT SPACE - Hoshino, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
We deal with self-organizing map models referred to as Kohonen type algorithm. In self-organizing maps, it is easy to observe some practical and interesting properties in the relation between the arrangement of the nodes and their values. We shall be concerned with behavior of ordering, state preserving properties and tendencies to be absorbed to a particular state in self-organizing maps with inputs taking values in an inner product space. We give a numerical example as its application and estimate ordering by simulation approach.